Pengaruh Manfaat Bangun Pagi, Kebiasaan Berolahraga, dan Gemar Belajar dari Tujuh Kebiasaan Anak Indonesia Hebat Terhadap Sikap Belajar Ekonomi Siswa Kelas XII SMA Negeri 5 Tana Toraja - Patioli, Santu R; Syarifuddin, Syarifuddin; W, Muhammad Fahreza (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2026)
This study aims to: 1) Determine and analyze the Effect of the Benefits of Waking Up Early from Seven Habits of Great Indonesian Children on the Economics Learning Attitudes of Grade XII Students of SMA Negeri 5 Tana Toraja. 2) Determine and analyze the Effect of Exercise Habits from Seven Habits of Great Indonesian Children on the Economics Learning Attitudes of Grade XII Students of SMA Negeri 5 Tana Toraja. 3) Determine and analyze the Effect of Love of Learning from Seven Habits of Great Indonesian Children on the Economics Learning Attitudes of Grade XII Students of SMA Negeri 5 Tana Toraja. 4) Determine and analyze the Effect of the Benefits of Waking Up Early, Exercise Habits, and Love of Learning from Seven Habits of Great Indonesian Children simultaneously on the Economics Learning Attitudes of Grade XII Students of SMA Negeri 5 Tana Toraja. This research approach uses quantitative research. The research was conducted on class XII students at SMA Negeri 5 Tana Toraja with the population in this study being class XII, totaling 288 from 8 classes multiplied by 36 students per class. The sampling technique used was purposive random sampling. Each class was represented by 10 people so that the total sample was 80 students. The data collection technique used a questionnaire and the data analysis technique used multiple regression techniques and t-test analysis and F test using SPSS  The results of this study are; 1). The probability value of X1 is 0.001. This value is smaller than 0.05 or the calculated t value is 3.401 t table 1.664 (n-1 = 79 alpha 5%) so it can be concluded that the variable Benefits of Waking Up Early (X1) has a positive and significant effect on the variable Attitude of Learning Economics of class XII students of SMA Negeri 5 Tana Toraja. 2). The probability value of X2 is 0.045. This value is smaller than 0.05 or the calculated t value is 2.040 t table 1.664 (n-1 = 79 alpha 5%) so it can be concluded that the variable Exercise Habits (X2) has a positive and significant effect on the variable Attitude of Learning Economics of class XII students of SMA Negeri 5 Tana Toraja. 3). The probability value of X3 is 0.000. This value is smaller than 0.05 or the calculated t value of 7.475 t table 1.664 (n-1 = 79 alpha 5%) so it can be concluded that the variable Love of Learning (X3) has a positive and significant effect on the variable of Economic Learning Attitude of class XII students of SMA Negeri 5 Tana Toraja. and 4). The sig. value of the F test is 0.000 at a significance level of 0.05. This value is smaller than 0.05 which indicates that all independent variables consisting of; Benefits of Waking Up Early (X1) Exercise Habits (X2) Love of Learning (X3) together influence the Economic Learning Attitude (Y) of class XII students of SMA Negeri 5 Tana Toraja/